Johannes Brøndsted - Jensen, Ole Klindt (Kuml, 1965)
JOHANNES BRØNDSTED Johannes Brøndsted gave the Jutland Archaeological Society his whole-hearted support and was an active participant from its inauguration. With due reason his advice was sought, for his talent and energy had been applied to so many ventures: Acta Archaeologica became, under his direction, a leading journal. He began an inspired teaching of archaeology in 1930 and in 1941 became the first professor of archaeology at Copenhagens University. Until then he had worked for the National Museum, also for its new image, and returned in 1951 as Director, to become the first Rigsantikvar in 1958. Much of this was new ground, but it seemed natural to his personality. He was the obvious and elegant host at the National Museum’s Anniversary in 1957 and could both describe 150 eventful years and point to the most recent advances with a vision of the future. Brøndsted was best known as a writer and scholar. He mastered the art of writing clearly and interestingly. In his youth, he made penetrating studies of art in the Viking period -a study which earned him his doctorate in 1920 (published in an enlarged version in English in 1924 with the title ’Early English Ornament’). Since then he has written erudite and lively books on the Vikings developing his ideas. The vast material of Danish antiquity was collected by him in a comprehensive and easily read work -’Danmarks Oldtid’ I-III, 1938-40, which is now in its 3rd edition. It was a great achievement to collect all this dispersed information in a great depiction of our early history. How large a material this is, can best be appreciated by comparing it with Worsaae’s hook of the same name from 1843 and Sophus Müllers ’Vor Oldtid’ from 1897. All three are imbued with the same enthusiasm and have given rise to further studies. Johannes Brøndsted died on 16th November, 1965, leaving a gap in Danish archaeology, of which he took so important a part. His style was both measured and warmly eloquent. He was a brilliant combination of a genuine Dane and a learned classicist. He had the assuredness home of a deep family background and spoke often of his childhood home and of his grandparents’, but not less vividly of the early communities, transformed through thousands of years of contact with the Danish countryside, which was the background also for his own family. Ole Klindt-Jensen.